If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 2 + -1a + -5 = 0 Reorder the terms: 2 + -5 + 3a + -1a = 0 Combine like terms: 2 + -5 = -3 -3 + 3a + -1a = 0 Combine like terms: 3a + -1a = 2a -3 + 2a = 0 Solving -3 + 2a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2a = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 2a = 0 + 3 2a = 0 + 3 Combine like terms: 0 + 3 = 3 2a = 3 Divide each side by '2'. a = 1.5 Simplifying a = 1.5
| 5n-2-2n=3n+14+6n | | 2x+4y=-4 | | 1/2=5/7+y | | 3/7=4/5+y | | 4d-9d+5d= | | y+3=.25+5 | | k^2-32k=0 | | 2.14c-4.5=3.6c-9 | | 6x-x+7=3+5x-9 | | 4/9s=12 | | 2/7t=6 | | 4/7y=12 | | 2/5r=6 | | (x+5)/2=15 | | 5.9=-7+x | | (N+7)=4n+28 | | 1/4(4x-8)+3/4(8x+4)=22 | | 4x^2-40x+100=36 | | 1/2x+3=4(0.125x+0.75) | | .43x-0.2=0.51x+0.36 | | 19-3x=4x+24 | | 4(x-6)+7=11 | | 5x-3/9=3x+7/5 | | 3x+25=180 | | 4x+2x=-x-12 | | 7h-4(h+3)=33 | | x=(cx+3)(c-2) | | 9x-12y=-21 | | 2ln*2x^2=6 | | 25-(3x-2)=25 | | 3*-3-5y=17 | | 4x^2-100=36 |